Utilization of Management Information Systems in Ensuring The Academic Quality of Vocational School - Yulan Tiarni Legistia; Nia Daniati; Ahmad Ahmad (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to know the utilization of management information systems through android application by teachers and students in ensuring the academic quality of the institution. The analysis used is qualitative approach that is by interpreting data interactively and continuously. Research data collection is done by interview, observation and document study. This research found that with the android application it can guarantee academic quality and make it easier for teachers and students to obtain academic information with a simpler system including attendance, evaluation, discussion and delivery of material. However, not all student attitudes can be observed through this application. This system is relatively new and needs further development in order to provide maximum benefits in an effort to ensure the academic quality of the institution.